Peran Pendidikan Agama Islam dalam Membentuk Karakter Bangsa - Anwar, Syaiful (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2016)
Character education must be grounded in basic human character that comes from universal moral values (absolute) sourced from revealed religion which is also called the golden rule. Character education can have a definite purpose when grounded in the values of the base character. According to psychologists some basic values of the character is the love of God and His creation (nature and content), responsibility, honesty, respect and courtesy, compassion, caring, cooperation, confident, creative, hard work and unyielding, justice and leadership, kind and humble, tolerance, love of peace, unity and love. Another opinion states that the basic character of man consists of: trustworthy, respect and attention, caring, honesty, responsibility, citizenship, honesty, courageous, diligent, disciplined, visionary, fair, and integrity (compare with the nature of the Prophet Muhammad).